Luminiscentne snovi - Županc Mežnar, Lea (Vakuumist, 1996)
In the article will be presented some of the properties of luminescent materials or phosphors: designation, colour, light output, persistence and morphology, as well as their preparation. Phosphors are widely used for displaying information in displays and for illumination purposes in fluorescent lamps.
Keywords: luminiscenca; luminiscentne snovi; lastnosti; sinteza